Facilitators and barriers to application of the Canadian C-spine rule by emergency department triage nurses. (July 2016) - Clement, Catherine M.; Stiell, Ian G.; Lowe, Maureen A.; Brehaut, Jamie C.; Calder, Lisa A.; Vaillancourt, Christian; Perry, Jeffrey J.
Highlights: Bringing about change in clinical practice is complex. Determination of facilitators and barriers to any clinical change is beneficial. Strong leadership, effective communication, and senior physician support are vital. Abstract: Objectives: We recently conducted a multicentre implementation study on the use of the Canadian C-Spine Rule (CCR) by emergency department (ED) nurses to clear the c-spine in alert and stable trauma patients ( n  = 4506). The objective of this study was to conduct a survey of nurses, physicians, and administrators to evaluate their views on the facilitators and barriers to the implementation of the CCR. Methods: We conducted both a paper-based and an electronic survey of the three different ED hospital staff groups of nine large teaching hospitals in Ontario, including six regional trauma centres. The content of this survey was informed by a qualitative evaluation of the opinions of the study nurses who had participated in the validation study. Results: 57.5% (281/489) ED triage nurses, 50.2% ED physicians, and 82.8% of administrators responded. Nurse responses most often showed support from manager/educators and teamwork between physicians, nurses, and managers as being important facilitators to the use of the CCR. Physician responses most often identified the importance of a nurse leader/champion/educator, and presence of strong physician leaders. Administrator responses indicated the importance of nurse educators/champions, nurse engagement, and educational support. Barriers indicated by all three groups included busy department, lack of physician support, and lack of nursing support. Conclusions: Bringing about change in clinical practice is complex. Strong leadership, effective communication, and senior physician buy-in appear to be very important. Identification of system-specific barriers and facilitators are important components of successful knowledge translation.